Nicotine-dependence-varying effects of smoking events on momentary mood changes among adolescents. (February 2015) - Selya, Arielle S.; Updegrove, Nicole; Rose, Jennifer S.; Dierker, Lisa; Tan, Xianming; Hedeker, Donald; Li, Runze; Mermelstein, Robin J.
Abstract: Introduction: Theories of nicotine addiction emphasize the initial role of positive reinforcement in the development of regular smoking behavior, and the role of negative reinforcement at later stages. These theories are tested here by examining the effects of amount smoked per smoking event on smoking-related mood changes, and how nicotine dependence (ND) moderates this effect. The current study examines these questions within a sample of light adolescent smokers drawn from the metropolitan Chicago area (N = 151, 55.6% female, mean 17.7 years). Instruments: Ecological momentary assessment data were collected via handheld computers, and additional variables were drawn from a traditional questionnaire. Methods: Effects of the amount smoked per event on changes in positive affect (PA) and negative affect (NA) after vs. before smoking were examined, while controlling for subject-averaged amount smoked, age, gender, and day of week. ND-varying effects were examined using varying effect models to elucidate their change across levels of ND. Results: The effect of the amount smoked per event was significantly associated with an increase in PA among adolescents with low-to-moderate levels of ND, and was not significant at high ND. Conversely, the effect of the amount smoked was significantly associated with a decrease in NA only for adolescents with low levels of ND. Conclusions: These findings support the role of positive reinforcement in early stages of dependent smoking, but do not support the role of negative reinforcement beyond early stages of smoking. Other potential contributing factors to the relationship between smoking behavior and PA/NA change are discussed. Highlights: Smoking results in higher positive affect at low-to-medium nicotine dependence. Smoking results in lower negative affect only at very low nicotine dependence. Smoking does not result in affect changes at high levels of nicotine dependence. Role of positive reinforcement in early stages of addiction is supported. Role of negative reinforcement at later stages of addiction is not supported.